PENGARUH NON PERFORMING LOAN DAN DANA PIHAK KETIGA TERHADAP KINERJA KEUANGAN DENGAN E-PAYMENT SEBAGAI VARIABEL MODERASI: Dibuat oleh Dessy Akhirana, Djauhar Edi Purnomo, Tutut Dwi Andayani (Dosen dan Mahasiswa FEB Universitas Muhammadiyah Pekajangan Pekalongan) - Tutut Dwi Andayani; Djauhar; Dessy Akhirana (Neraca, 2021)
This study was conducted to determine and analyze the effect of Non-Performing Loans and Third Party Funds on ROA, and to determine the moderating effet of the E-payment variable on the effect of Non-Performing Loans and Third Party Funds on ROA, in banking companies. The independent variables used in this study were NPL and Third Party Funds; the dependent variable was ROA; and the moderating variable was E-payment. This srudy was quantittative study using a population of 43 Conventional Commercial Banks in Indonesia in the period of 2019-2020. The sampling technique used was a purposive samplinng method so thata sample of 28 conventional commercial banks in Indonesia in 2019-2020 was obtained, resulting to the total sample of 56 banking companies. The data analysis technique used in this research was Moderated Regression Analysis and the hypotheses were tested by using SPSS 16.0. The results of the analysis revealed that (1) NPL had a significant negative effect on ROA (2) Third Party Funds had no significant effect on ROA (3) E-payment was not able to moderate or weaken the effect of Non-Performing Loans on Return On Assets and (4) E-payment was able to strengthen Third Party Fund on Return On Assets. Keywords : Non Performing Loan, Third Party Funds, E-PaymenT, Return On Assets